Caracterização molecular de amostras de Pseudomonas spp. resistentes aos carbapenens isoladas de infecções de corrente sanguínea em hospitais brasileiros - Catan, Thais Avila Fernandes [UNIFESP] (2017)
ABSTRACT Infections caused by Pseudomonas spp. has become a challenge for clinicians due to their intrinsic resistance as well as their incredible ability to acquire antimicrobial resistance genes associated with their virulence. In this context, the dissemination of P. aeruginosa strains ST277 carrying blaSPM-1 gene among Brazilian hospitals increased the carbapenems resistance rates. In addition, cross-resistance with other classes of antimicrobials found in these epidemic strains confers the multidrug resistance (MDR) phenotype. Due to the Brazilian continental proportions, epidemiological studies that aim to evaluate the resistance mechanisms among bacterial isolates at a national level are extremely important. Thus, the present study aimed to molecularly characterize the carbapenem-resistant Pseudomonas spp. clinical isolates from bloodstream infections (BSI) recovered from patients admitted to different Brazilian medical centers. All Pseudomonas spp. isolates sent by participating medical centers had their re-identification and antimicrobial susceptibility testing performed by the BD Phoenix® 5.1 TM automated system. Subsequently, those isolates that showed resistance to imipenem and meropenem had their identification at the species level confirmed by MALDI-TOF MS. Minimum inhibitory concentrations for 10 antimicrobials were calculated by broth microdilution technique, and the genetic similarity of all carbapenem-resistant isolates was performed by PFGE technique. Genes encoding for acquired resistance to β-lactams, aminoglycosides, and quinolones were investigated by PCR followed by sequencing. Between 2007 and 2011, 280 Pseudomonas spp. isolates were recovered from BSI were sent by the 14/16 hospitals participating in the Brazilian SCOPE Project, being one isolate per patient. The majority of Pseudomonas spp. isolates was recovered between 2008 and 2009. The patient’s age ranged from 31 days to 92 years, with most of patients being male (52%). A mortality rate of 57% was observed among patients with BSI caused by Pseudomonas spp. in the present study. According to the susceptibility profile obtained by BD Phoenix®, 32% (n = 87/271) of the isolates were considered resistant to carbapenens. Of these, only 57 (65.5%) were evaluated for the production of carbapenemases and the genetic similarity profile evaluated by the PFGE technique, since 30 isolates were excluded from the study because they were no longer viable or because they did not confirm resistance to both carbapenens by broth microdilution technique. All isolates resistant to both carbapenems were identified as P. aeruginosa, with the exception of a single isolate whose identification was inconclusive among Pseudomonas monteilii/mosselii by MALDI-TOF MS technique. Only polymyxin B showed activity against all carbapenem-resistant Pseudomonas spp. isolates (MIC50 = 0.5 μg/mL). MβLs were detected in 63.1% of the isolates (n=36/57). The blaSPM-1 was the most frequent gene, present in 39% (n=32) of the isolates, followed by the blaIMP-like genes (n=4; 7%). The isolate identified as P. monteilii/mosselii showed MICs for imipenem and meropenem of 1 μg/mL (S) and 32 μg/mL (R), respectively, and carried the blaIMP-16-like gene. The blaSPM-1 gene was found in all the states evaluated in the study. Due to the co-production between SPM-1 and RmtD found in most isolates, the rmtD gene also showed a high frequency. On the other hand, some resistance genes were found restricted to certain hospitals and/or geographic regions, such as blaGES-16 (DF), blaGES-1 (RS), blaIMP-1 (SP), blaIMP-16-like (SP), blaCTX-M-14-like and rmtE (CE). Co-productions of RmtD+GES-1+SPM-1, RmtD+CTM-M-1/2 and RmtD+CTX-M-14 were observed. The rmtE gene was detected in a single isolate that also carried the blaCTX-M-1/2 gene. The 53 carbapenem-resistant isolates were grouped into 11 clonal groups (A to K), with a similarity ≥80%. Most of the isolates belonging to clone A were SPM-1+RmtD producers and were distributed in five states. In this clone, the isolates producing IMP-1, CTX-M-14+RmtD and GES-1+SPM-1+RmtD were also included. The present study demonstrated that the production of SPM-1 continues to be the main mechanism of resistance to carbapenens verified in P. aeruginosa isolates that cause BSI in Brazil. In addition, the spread of intra- and inter-hospital epidemic clones is of concern, and the emergence of new resistance mechanisms observed in our study highlights the urgency of establishing a national surveillance program for antimicrobial resistance in bacteria and the implementation of effective measures in controlling MDR pathogens.